A review of the relevance of bottle gourd in Eastern and Southern African traditional music, and social life - Olufunke O. Fajinmi; Olaoluwa O. Olarewaju; Georgina D. Arthur; Roger M. Coopoosamy; Kuben Naidoo (AOSIS, 2022)
Background: The history of several communities and tribes in Africa is incomplete without emphasising on the crucial role of the Cucurbitaceae family, especially the calabash or dried gourds, in Africa. The plant is extensively used in several traditional ceremonies and spiritual exercises, and in the production of various traditional African musical instruments which proffer economic incentives to stakeholders. Aim: To discuss the relevance of the bottle gourd in Eastern and Southern African nations in relation to the production of traditional musical instruments; the uses and impacts of the traditional musical instruments; and their morphology. Methods: A literature search was conducted on electronic databases such as Google Scholar, Google books, Scopus, and Web of Science. The search was performed using several terms and free text words, combining them in an appropriate manner. The authors further set inclusion and exclusion criteria to screen for relevant articles. Each of the identified articles was independently reviewed to determine eligibility and to extract study information. Results: The African continent has a deeply rich and fascinating traditional and cultural heritage such as ancestral worship, cleansing ceremonies, spiritual ceremonies, intervillage ceremonies and competitions, and royal ceremonies like enthronement of kings, royal weddings, royal funerals, and appeasement of the gods. Traditional musical instruments made with gourds (as the resonator) are prominently played during these ceremonies and spiritual exercises. The ceremonies are often accompanied by chanting and singing whilst traditional musical instruments such as rattles made of gourds or chordophones, in which gourds are used as resonators, are played. Conclusion: Bottle gourd is an important raw material in the assemblage of several Southern and Eastern Africa traditional musical instruments and is highly revered in the socio-cultural ceremonies and spiritual exercises of several tribes and communities across these regions. Hence, bottle gourd plays a vital role as a bedrock of the culture, social and spiritual life of these people and therefore reflects in the history and daily life of the Southern and Eastern Africans.